The dilemma of Tax Reform: ¿structural or fiscal? (2017)
On October 20, the Minister of Finance, Mauricio Cárdenas, presented tothe Congress the law project on tax reform, largely based on the report of the Commissionof Tax Experts. The national government aims to raise $ 7.2 billion and thus compensate the reduction in the Nation’s income caused by factors such as the fall inoil prices, the reduction of economic growth, which - according to projections for 2016 of theBank of the Republic, can be around 2% -, and the elimination of temporary taxes from 2018.